THE EFFECT OF SONG MEDIA IN PRONUNCATION SKILL AT CLASS VIII SMP NEGERI 1 BADAR THE ACADEMIC YEARS 2023/2024 2023/2024 - Lasmaria Lasmaria; Wikiaprian Pinim; Wahyu Fatahillah (STKIP USMAN SAFRI KUTACANE, 2024)
A Thesis English Education Department the Faculty of Teachers Training and Education, stkip us Kutacane.The aim of the research was to find out the effect of song media in pronounciation skill. This research was done on 10th July until 10th August 2023. The population of this research are 191 students from all VIII Class. The sample was taken purposive sampling which is only choose one class.The sample are the students of VIII A Class which consist of 32 students. The research gave two tests, they are pre test and post test. The data was collected by using Rubric of Pronunciation which focus on Consonant, Vowels, Intonation, Rhythm and Stress.The data was analyzed by using t-test. The minimus completeness criteria in learning English for National Senior High School at SMP Negeri 1 Badar is 70. It was found that the pre test average is 45,75 and the post test average is 75,62. The data had been calculated by using t-test, the researcher found that t observation = 30,18 by seeing the t table with df n-1 of level α = 5%, it was found that t table = 1,696. It means the t observation is bigger than t-table = 30,18 > 1,696. So the rearcher took the conclusion that the hypothesis alternative in this research is received. There is a significant progress of students’ ablitiy in learning pronunciation by using Song as media on VIII A Class at SMP Negeri 1 Badar in the Academic Years 2023/2024.